ENTEROVIRUS INFECTION IN CHILDREN: CLINICAL AND EPIDEMIOLOGICAL FEATURES AT THE CURRENT STAGE - G. P. Martynova; I. A. Kutishcheva; E. B. Boytsova; O. A. Gura; A. A. Andreeva (LLC "Diagnostics and Vaccines", 2016)
The article presents the current clinical and epidemiological features of enterovirus infection in children of Krasnoyarsk Territory. A retrospective analysis of the incidence of enterovirus infection and enterovirus meningitis in the period 2014-2015 according to the forms of state statistical reporting №2 «Information on infectious and parasitic diseases». Clinical and epidemiological analysis of enterovirus infection in 454 children who were treated at MBUZ «City Children's Infectious Hospital №1» in the period of seasonal rise of morbidity in 2014 revealed a prevalence of etiological structure of enteroviruses Coxsackie B, Coxsackie B5, Coxsackie B3, Coxsackie B4. The region recorded the different clinical forms of enterovirus infection (rash, myalgia, diarrhea, gerpangina), the structure of which is still, aseptic meningitis prevails.